50.9k views
3 votes
Standard form Ax+By=C

Standard form Ax+By=C-example-1

2 Answers

6 votes

3x - 20y = 36

multiply through by the lowest common multiple of 3 and 4, that is 12

20y = 3x - 36

subtract 3x from both sides

- 3x + 20y = - 36

In standard form the coefficient of x must be a positive integer.

multiply all terms by ( - 1)

3x - 20y = 36 ' in standard form '



User Stephane Rolland
by
5.9k points
0 votes

Given (5/3)y = (1/4)x - 3, we rearrange these terms so that the equation appears like Ax + By = C:

-(1/4)x + (5/3)y = -3 This is the equation in "standard form."

User Blondie
by
6.7k points